THE IMPACT OF TEACHER SERTIFICATION ON TEACHER PERFORMANCE IN SCHOOL - Sudarmono Sudarmono; Maisah Maisah; Ahmad Fikri; Neneng Hasanah (Dinasti Publisher, 2021)
Teacher certification is one form of implementation of Law Number 14 of 2005 concerning Teachers and Lecturers by providing teacher certificates to teachers who have met certain requirements, namely having academic qualifications, competence, being physically and mentally healthy, and having the ability to realize national educational goals, followed by an increase in decent welfare. Teacher certification aims to increase knowledge, performance, creativity, and be able to carry out other main tasks and functions related to the teaching and learning process . Based on the background of the problem above, researchers are interested in revealing this phenomenon in a study. The purpose of this study was to determine the impact of teacher certification on teacher performance in schools, especially at SMAN 5 Jambi City. This type of research is field research using a qualitative- naturalistic approach . Through this qualitative approach, it is hoped that a picture of the quality, social reality and perceptions of the research objectives will be lifted without being contaminated by formal measurements . The subjects in this study were 60 certified teachers in State Senior High School 5 Jambi City. The required data is obtained through interviews, observation and documentation.